2005
DOI: 10.1016/j.ymgme.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of optimal dietary therapy upon visual function in children with long-chain 3-hydroxyacyl CoA dehydrogenase and trifunctional protein deficiency

Abstract: The objective of this prospective cohort study was to determine if dietary therapy including docosahexaenoic acid (DHA; C22:6ω-3) supplementation prevents the progression of the severe chorioretinopathy that develops in children with long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) or trifunctional protein (TFP) deficiency. Physical, biochemical, and ophthalmological evaluations, including electroretinogram (ERG) and visual acuity by evoked potential (VEP), were performed at baseline and annually following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 40 publications
6
68
1
4
Order By: Relevance
“…In the present study, half of the patients initially demonstrated subtle general pigmentations spread in the posterior poles and in the mid-periphery and not in the macular areas, a finding also described by Gillingham et al (2005). In the children with macular pigmentations, the darker appearance of the macular region may be partly the result of perimacular atrophy, which increases the contrast to the surrounding retina.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, half of the patients initially demonstrated subtle general pigmentations spread in the posterior poles and in the mid-periphery and not in the macular areas, a finding also described by Gillingham et al (2005). In the children with macular pigmentations, the darker appearance of the macular region may be partly the result of perimacular atrophy, which increases the contrast to the surrounding retina.…”
Section: Discussionsupporting
confidence: 73%
“…The sum of long-chain hydroxyacylcarnitine concentrations, a measure of partial fatty acid oxidation metabolites in subjects with LCHAD or TFP deficiency and an indicator of metabolic control, did show a non-significant trend toward increased levels in the fasting state but postprandial AUC levels were not different. A rise in hydroxyacylcarnitine concentrations with a high protein diet could be detrimental to long-term outcomes even if it prevents obesity [8]. Further long-term study is needed to determine the metabolic safety of a high-protein diet in individuals with fatty acid oxidation disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Nine subjects, seven years of age or older, with a conWrmed diagnosis of LCHAD or TFP deficiency were recruited from a previous cohort for this study [7,8]. Six cases had previously published mutation analyses [9][10][11][12].…”
Section: Subjectsmentioning
confidence: 99%
“…Der Erhalt des Gesichtsfelds war dabei direkt mit der Normalisierung des DHASpiegels im Blut korreliert. Ähnlich dazu korrelieren hohe Plasma-DHA-Konzentrationen nach Nahrungsergänzung mit dem Erhalt der Netzhautfunktion und Sehschärfe bei Kindern mit langkettiger 3-Hydroxyacyl-CoA-Dehydrogenasedefizienz [22] …”
Section: Docosahexaensäure (Dha)unclassified